PSYCHOLOGICAL AND PEDAGOGICAL FEATURES AND CLASSIFICATION OF COMMUNICATIVE COMPETENCIES IN THE FORMATION OF JUNIOR SPECIALISTS IN COMPUTER SCIENCE LESSONS - A. R. Yuldashev; M. A. Madrakhimova (Galaxy International Interdisciplinary Research Journal, 2023)
The essence of competence and competence as a pedagogical phenomen and the idea of competence approach as a factor of increasing effecience of education have been presented in the article.